Assessment of the Bangladeshi antibiotic market: Implications of the WHO AWaRe classification and dosage form availability on antimicrobial resistance - Joya Rani; Sudipta Saha; Fahmi Ferdous; Md. Ajijur Rahman (Elsevier, 2024)
Background: Availability of antibiotics without prescription contributes to the rising threat of antibiotic resistance due to widespread self-medication and improper use. In this study, we aimed to assess the antibiotic market in Bangladesh according to the WHO AWaRe (Access, Watch, Reserve) classification system to better understand how the unregulated access of antibiotics may influence self-medication practices and the emergence of antibiotic resistance in the country. Methods: Data on AWaRe class antibiotics, their strengths, and dosage forms were collected from Bangladeshi drug indexing smartphone applications, the Bangladesh National Formulary (BDNF), and the Directorate General of Drug Administration (DGDA) website. Sales data were analyzed using IQVIA data to determine the market value and compound annual growth rates (CAGR) of antibiotics. The analysis focused on categorizing antibiotics according to the WHO AWaRe classification and examining their availability in various dosage forms and strengths including child-appropriate formulations. Results: Of the 81 antibiotics available in Bangladesh, 54.32 % belong to the Watch class, 30.86 % to Access, 8.64 % to Reserve, and 6.17 % were unclassified. In terms of ATC classifcation, the majority (91.35 %) belonged to the J01 class. Most antibiotics were available in multiple dosage forms and strengths, with tablets (54.87 %), injections (48.78 %), and capsules (30.48 %) being the most common. Additionally, 35.8 % of antibiotics were available as child-appropriate formulations. Oral formulations were prevalent, with 88.0 % of Access, 75.0 % of Watch, and 28.57 % of Reserve class antibiotics were available in oral dosage forms. A total of 56 antibiotic combinations were identified, including six WHO-recommended and two WHO-not-recommneded fixed-dose combinations. Watch class antibiotics dominated the market in terms of sales value and CAGR. Conclusion: The widespread availability of Watch class antibiotics, particularly in oral and child-appropriate formulations suggest a need for stricter regulation and public health interventions to curb self-medication, inappropriate marketing and use of antibiotics to mitigate the risks of resistance.